Planarized Trench Isolation of In0.52Al0.48As/In0.8Ga0.2As Metamorphic High-Electron-Mobility Transistor by Liquid Phase Chemical Enhanced Oxidation - Houng-Wei Chen (IEEE, 2021)
The liquid phase chemical enhanced oxidation (LPCEO) technique was applied to achieve planarized isolation of a high-indium-content In0.52Al0.48As/In0.8Ga0.2As metamorphic high-electron-mobility transistor (MHEMT). Through a simple, low-temperature process not requiring costly machinery, electrical isolation of components was accomplished. In addition, multiple advantages were gained, including the production of planarized surfaces, low pollution, and reduction in the subsequent disposal of wet etching solution and costs for dry etching or ion implantation. Because of the decrease in lateral defect density caused by wet or dry etching and the further decrease in gate leakage current owing to the isolated oxide film, the performance of devices, with improved DC characteristics, less flicker noise, and enhanced high-frequency performance, can be increased.